Market Structure and Competition in the Banking Industry : A Review of Literature - Chandanani, Priyanka; Singh, Kalpana; Majumdar, Sudipa (Indian Journal of Finance, 2017)
The significance of the banking industry in the economy has generated a vast body of research on the study of competition within the industry. Especially with the deregulation and subsequent re-regulation of the banking sector in a large number of economies as well as the constant attempt towards consolidation via mergers and acquisitions, the changing structure of this crucial sector has become an area of interest for researchers. Traditional economic theory supports the view that efficient market structures facilitate competition in an industry. With this as base, the current paper discussed the theoretical foundations of measuring competition; it discussed the classical industrial organization theory on market structures in banking via the Structure-Conduct-Performance paradigm as well as the neo-industrial organization approach towards the structure in the banking industry. It reviewed the literature on previous studies that were conducted in this regard to measure competition and market structure in the banking industry with a view to identify the scope for further research on the changing market structure of the Indian banking sector.